Direct observational evidence for disturbance dynamo on the daytime low‐latitude ionosphere: A case study based on the 28 June 2013 space weather event. Issue 10 (8th October 2016) - Thampi, Smitha V.; Shreedevi, P. R.; Choudhary, R. K.; Pant, Tarun Kumar; Chakrabarty, D.; Sunda, S.; Mukherjee, S.; Bhardwaj, Anil
Abstract: A case of the westward disturbance dynamo (DD) electric field, influencing the daytime equatorial and low‐latitude ionosphere, during a geomagnetic storm that occurred on 28–29 June 2013 is presented. The GPS total electron content (TEC) observations from a network of stations in the Indian equatorial, low and middle latitude regions along with the radio beacon TEC, ionosonde, and magnetic field observations are used to study the storm time behavior of the ionosphere. Negative ionospheric storm effects were seen over the low and middle latitudes during the storm time due to the presence of a westward DD electric field. Observations show that the suppression of the equatorial ionization anomaly (EIA) from the morning hours itself on 29 June 2013 took place due to the prevailing westward DD electric field, providing evidence for the model calculations by Balan et al. (2013). Simulations using the GITM model also agree well with our results. The present study gains importance as the direct observational evidences for disturbance dynamo effects on the daytime low‐latitude ionosphere and the EIA are sparse, as it has been difficult to delineate it from the compositional disturbances. Key Points: Observational evidence for the westward DD electric field affecting the daytime low‐latitude ionosphere EIA is suppressed due to the westward electric field prevailing from morning hours GITM model simulations agree with the observations